High temperature deformation behavior of Mg67Zn28Ca5 metallic glass and its composites - Fu, X. L. (2016)
Mg67Zn28Ca5 amorphous alloy specimens with various volume percentage of crystalline phases were obtained by annealing fully amorphous alloy at slightly above crystallization temperature. Strain rate effect of flow stress of Mg67Zn28Ca5 amorphous alloy and its composites at supercooled liquid region were studied. The strain rate sensitivity m for monolithic metallic glass can approach 1, but all the composites have lower strain rate sensitivity (~0.17). After a prolonged testing period, the deformation mode of Mg67Zn28Ca5 based composites changed from superplastically into fragmentation mode. Glassy Mg67Zn28Ca5 exhibits the best superplasticity and thermal stability compared to its devitrified composites.